Può la meditazione andare oltre la divisione soggetto-oggetto della modernità? Sulle tracce ereditate dal XX secolo - Cipolletta, Patrizia (B@belonline, 2024)
In modern times, the West broke with the Greek and Eastern circular temporality, and introduced the expectation, present in different forms in both Judaism and Christianity, of an ultimate future time. Modernity was born along this line with the idea of the gradual possession of nature and of a knowledge that renounced the revelation of everything that is, but postponed it in a path that should have progressed in time. Thus, a train has left, a train that today travels at 3000 km per hour, by which we progressively know nature and manipulate it. A train that always increases in speed but that now cannot be stopped and from which we cannot get off, although the time of progress has been questioned, although we are now aware that we cannot know all things. The essay takes into consideration the fact that the reification and manipulation of things in nature, and of the nature that we ourselves are, arises from the separation of mind and body. Here, we do not propose a cognitive study of the connection between the mind and the body, but we address the discomfort of this split in hyper-modernity. Certainly, the use of Eastern meditative practices allows a break from the rush of our times, a break that fosters a mind-body reconnection. But meditation in the West cannot ignore the fact that we are on a train that travels at high speed, it cannot ignore the legacy of critical thinking. This essay tries a path of mind-body reconnection suitable for our world, to start a change in our manipulative way of human things.